The Transformation of the Structure and Function of al-Qurbā and Its Consequences for the Mother’s Position in the Guardianship System - Devy, Soraya; Habibi MZ, Muhammad; Muliana, Muliana; Fauzani, Laitani (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The role of mothers has become increasingly prominent in exercising authority to fulfill their responsibilities in caring for orphaned children and managing their property. This study is motivated by the fact that traditionally, al-qurbā (close relatives) such as grandfather, paternal uncle, and other paternal kin have been entrusted with the care, management, and development of orphans and their property, without recognizing the position of the mother in the guardianship structure. Hence, the study aims to explore the transformation of the structure and function of al-qurbā and its effects on the status of mothers in the guardianship system. This study employed a qualitative research method using a conceptual analysis approach to normative legal issues. Data were collected through a mixed approach, combining field research conducted by means of observation and interviews in Banda Aceh and Aceh Besar with library research to identify relevant. The findings reveal that the transformation of the structure and function of al-qurbā within the guardianship system has occurred through two models. The first one is natural transformation, which is related to cultural factors, family structure, gender issues, modernization, and local traditions. The second is scholarly transformation, which encompasses legal reforms, government policies, and developments in legal scholarship, including the attempts to reformulate the concept of guardianship by means of holistic interpretation of Qur’anic verses that were previously interpreted in a partial manner. Further, three main consequences of these transformations have been identified in this study, including: the elevation of the mother’s position in the order of guardianship, the changes in the mother’s authority as a legal guardian, and the modifications to the rights and responsibilities assigned to the mother upon her appointment as the guardian of an orphaned child.